Ruptured Basilar Artery Perforator Aneurysm: Nightmare of a Treating Neurosurgeon - Sarma, Pragyan; Agrawal, Atul; Sharma, Amit Kumar (Asian Journal of Neurosurgery, 2025)
Objectives Subarachnoid hemorrhage (SAH) resulting from rupture of basilar artery perforator aneurysm (BAPA) is a neurological rarity. With increased awareness and advancements in imaging modalities, they are now more frequently detected. However, concerns regarding their suboptimal treatment and lack of proper analysis still exist. We are hereby reporting our experience of treating this entity in a small cohort.Materials and Methods It is a retrospective study of all the cases of SAH resulting from rupture of BAPA, which were treated by the same surgical team. Demographic data, treatment characteristics, and follow-up data of our cases along with published literature were studied.Results Our cohort comprised of five patients (mean age 55 years). Three cases were treated with flow diverter alone and the rest underwent flow diverter and overlapping stent placement. Initial diagnostic cerebral angiography (digital subtraction angiography) was negative in three of them. There was one mortality and favorable outcome was encountered in the remaining cases. All of them demonstrated complete occlusion of the aneurysm in follow-up.Conclusion Following treatment, all the cases demonstrated complete angiographic occlusion of the aneurysm. In available literature, studies have small sample sizes. Future randomized studies in a larger cohort and proper reporting and analysis of outcomes will help us formulating a treatment protocol for BAPA.
Keywords: BAPA; DSA; FD; SAH; DAPT